Ecologia de aves de campos hidromórficos do cerrado: monitoramento de populações, espécies ameaçadas, variações estacionais e sucessão em áreas atingidas pelo fogo - Pioli, Dimas (2017)
Fire is a structuring agent of the Cerrado biome, provided it is not too frequent, the largest savannah in South America. Its grasslands are home to several vulnerable species of birds and are among the most threatened types of habitat in Brazil. Six areas of wet grasslands were studied in central Brazil, three that had been burned one month earlier and three untouched by fire for at least three years. In each area, five 200 m long transects with one watch point at the end were chosen, totaling thirty points. They were surveyed for a period of twelve months, starting in October, 2015. The ecological succession of grassland birds was monitored and the True Diversity index compared using an ANOVA test. The differences between burnt and unburned treatments, between rainy and dry seasons and for their interaction were significant (f = 5.542, p = 0.022; f = 5.909, p = 0.0183; f = 5.699, p = 0.021; respectively). The life histories of the bird species were observed, along with the environment variables. Several vulnerable species were not recorded in areas recently burned, while one was recorded only in burnt areas. Some causes could be attributed to the dynamics of food availability, humidity and degree of soil cover by the vegetation. These species began to frequent recovering burnt areas, taking advantage of seed producing grasses and flowering throughout the dry season. Migratory birds were present only in the wet summer, departing with different timings at the beginning of the dry period and returning only at the end. Detection of grassland birds was greatly reduced in late summer and early dry season. This was due to the more discrete behaviour after the reproductive period and because the vegetation had become very high, also hindering visual records. The data on the species focus of this , Alectrurus tricolor (Vieillot, 1816), corroborate reports and a simulation that attribute to it the status of resident. Evidence suggests that at least some pairs stay together throughout the winter. Males were recorded exhibiting their exotic tails in every month. Like other species, the birds adopted reclusive behaviour and the detection of females required extra effort. This study suggests the need for more in-depth studies on the ecological dynamics of the wet grasslands of the Cerrado. It also points to the urgent need to preserve these vital environments, preferably by creating protected areas, highly scarce. The use of agricultural areas by various species attests to the importance of management planning for the entire matrix.